Female Welfare & Christian Missions in Urdu Novel - Dr. Sumaira Umar (Zaban-o-Adab, 2024)
several centuries resulting a desired social status of women in 19th century. The technological advancements and proliferation of global capitalism played a vital role to accelerate this change. Christian Missions took part in enhancing the status of Indian women. The story of these changes is documented in Urdu novel. A number of Urdu novels presented a theme of female vulnerability after she decided to leave the house and took part in different economic activities. The Christian missions took great interest in reforming female world and also provided shelters for the vulnerable females who were homeless or lost families due to some unavoidable circumstances. By closely reading the novelistic texts I argue that Christian Missions in colonial India were bringing social change for females through education and job creation. They were also, although at a small scale, bringing economic independence by enhancing different skills and also becoming the sanctuaries for homeless females.